Evaluasi Hasil Belajar Matematika melalui Media Interaktif RStudio dengan Uji Wilcoxon - Roberto Abi; Justin Eduardo Simarmata; Yohanes Jefrianus Kehi (Prodi Pendidikan Matematika STKIP Persada Khatu;istiwa Sintang, 2026)
Mathematics learning is often considered difficult by students because the concept is abstract, especially the topic of systems of linear inequalities in two variables (SPtLDV). The limitations of visualization in conventional learning lead to low conceptual understanding and impact student learning outcomes. Learning media that can present interactive visual representations are needed to help students understand mathematical concepts concretely. This study aims to evaluate students' mathematics learning outcomes after using RStudio-based interactive learning media on the topic of SPtLDV. This study used a quantitative approach, involving 36 grade X students of SMA Negeri 1 Kefamenanu. Learning outcome data were obtained through pretest and posttest. Data analysis was carried out using descriptive statistics, boxplot visualization to illustrate data distribution, and the Wilcoxon signed-rank test at a significance level of 5% to test the difference in scores before and after learning. The results of the analysis showed that the average posttest score was higher than the pretest, accompanied by a shift in the distribution of scores towards a higher direction in the boxplot visualization. The Wilcoxon signed-rank test showed a significant difference between the pretest and posttest scores (p < 0.05). These findings indicate that the use of RStudio-based interactive learning media is associated with improved student learning outcomes the topic of SPtLDV. This research contributes to the development of statistical software as an interactive visualization medium to support mathematics learning at the secondary school level.Keyword: Interactive Learning Media, RStudio, Mathematics Learning Outcomes.